PENGARUH BELANJA PEMERINTAH TERHADAP PRODUKSI SEKTOR USAHA MIKRO MENENGAH DI MASA PANDEMI COVID-19 MENGGUNAKAN MODEL STATISTIK - Dandy Ananda Patria Wirawan; M. Heru Akhmadi (LPPM Universitas Bina Bangsa, 2023)
Various policies have been implemented to reduce poverty levels after the COVID-19 pandemic. The government focuses on increasing government spending in various sectors, especially in the economic sector. Government Expenditure Allocation Economic Function continues to be increased in order to maintain national economic stability through various programs. The capital program for MSME actors, by channeling financing with installments and low interest, namely Ultra Micro Financing (UMi). The provision of assistance to Micro, Small and Medium Enterprises (MSMEs) aims to maintain the continuity of the business being run. With the movement of the economic wheels at the smallest level, it is expected to provide a multiplier effect on economic growth. Based on the results of previous research, it is known that the Realization of Government Expenditure on Economic Functions has a significant effect on the realization of GDP. However, how will it impact the COVID-19 pandemic? The purpose of this study is to determine the effect of Central Government Expenditure on Economic Function on the Production of Small and Medium Enterprises. The study used multiple linear regression method with panel data from 34 provinces in Indonesia. The data period used is 2019-2021. The independent variables used are Average Length of Schooling (RLS), Number of Cooperatives, UMi Financing Distribution, and Realization of Government Expenditure on Economic Functions. While the dependent variable uses the Annual Production Increase of Micro Enterprises. From the test results, it can be concluded that the Realization of Government Spending on Economic Functions can have a significant and positive impact on the Production of Small and Medium Enterprises during the COVID-19 pandemic